RELIGION AND EDUCATION FOR LIFE - Amarnad, Anto (Journal of Dharma, 2006)
History has never been stable in reporting what is barely optimistic in the genuine development of humanity. But, it has always been an accumulated record of the ups and downs in human progress that expressed the genuineness and hypocrisy, goodness and wickedness of the human spirit. History, in ancient times, was more or less concerned with the annals of kingdoms, religious activities, and occasionally about the narrations of revolt and revolution in human societies. However, in ancient times, the religion had the central role to play in human life by determining and controlling men and women and the society from within and outside, and most of their activities. Consequently, religion played scores of roles for giving purpose and meaning to each human being. When people with moral and affirmative outlook controlled the religion, it constantly guided men and women for the constructive augmentation of everything that was genuine. But when the institution of religion was controlled by the immoral and selfish minds, the outcome became too pathetic and destructive for human integrity and dignity. Thus, history of religion was swarming not only with constructive events but also with negative episodes.